Two-step widefield fundus fluorescein angiography-assisted laser photocoagulation in pediatric retinal vasculopathy: A pilot study - Peng, Jie; Ren, Jianing; Zhang, Xuerui; Yang, Yuan; Zou, Yihua; Xiao, Haodong; Xu, Yu; Zhao, Peiquan (Frontiers in Medicine, 2022)
Purpose: To introduce the procedures of two-step fundus fluorescein angiography (FFA) and evaluate its utility in management for pediatric retinal Vasculopathy. Methods: In this retrospective study, medical records of 12 patients received two-step FFA were studied. The two-step FFA consisted of a step 1(low-dose, LD) FFA at an intravenous dose of 1.5 mg/kg fluorescein, followed by step 2(reduced dose, RD) FFA at a dose of 6.2mg/kg fluorescein. Demographic data including age, gender, diagnosis, weight, gestational age, birth weight and weight on the exam day were taken were collected. The results of two-steps FFA and treatment were recorded. Results: A total of 20 eyes were studied. The top 5 common FFA changes in RD-FFA included peripheral avascular zone (15 eyes), fluorescein leakage (10 eyes), supernumerous vascular branching (10 eyes), neovascularization (NV) (8 eyes) and absence of the foveal avascular zone (6 eyes). LD-FFA was efficient to show all NV without severe vitreous dye in 8/8(100.00%) eyes with NV, partial peripheral avascular zone in 11/15(73.33%) eyes, while RD-FFA always offered more information in all eyes. Fourteen eyes had laser photocoagulation under the guidance of LD-FFA. In 4 (4/14) eyes, RD-FFA revealed more lesions and immediate re-laser was performed. After a median follow-up of 28 months, all eyes were in a stable status. Conclusion: Step-one LD-FFA acted as a pre-FFA to show the NV, and a step-two RD-FFA as a double-check. The modified strategy may be a helpful clinical adjuvant in the laser treatment of pediatric retinal disorders, especially for young ophthalmologists.